ARRAYS: HAS THE TIME COME FOR HAEMATOLOGICAL MALIGNANCY?. (February 2015) - Kaub, Peter A.; Fletcher, Janice M.; Moore, Sarah
Abstract : Single nucleotide polymorphism (SNP) microarray technology allows elucidation of a virtual karyotype at much greater resolution than traditional cytogenetic techniques. The size of deletions of a bi- or mono-allelic nature, clone size and concomitant abnormalities can be assessed in a single test. Is array therefore inherently better than traditional karyotyping? At what stage should it become the new standard of care? A case presentation for a patient with chronic lymphocytic leukaemia (CLL) will be presented to provide the evidence for advantages of SNP array over classical karyotyping. A summary of recent CLL cases analysed by SNP array from our centre will be discussed in terms of diagnostic and prognostic value, supporting the case that, at least for CLL, SNP arrays are ready to supplant classical karyotyping for diagnosis.